Standardisierte histomorphologische Aufarbeitung von Peritonealbiopsien im Rahmen des Deutschen Peritonealbiopsieregisters (GRIP, German Registry In PD) - Pfister, Frederick; Büttner-Herold, Maike; Kitsche, Benno; Bulian, Dirk R.; Kielstein, Jan; Wanninger, Reinhard; Eden, Gabriele; Alscher, Dominik; Nebel, Michael; Schwenger, Vedat; Amann, Kerstin Ute (Pathologe, 2020)
The peritoneal lining of the abdominal cavity consists of a parietal and visceral sheet. The serosa is an interesting organ, which in medical practice is particularly important in the context of chronic peritoneal dialysis (PD). This method of renal replacement therapy utilizes the semipermeability of the peritoneal surface by applying PD solutions of differing osmolarity to eliminate toxic substances and regulate fluid and electrolyte equilibrium. This method is an ideal approach especially for younger patients and is very effective at least for some time. Pre-existing injury to the peritoneum, for example as a consequence of chronic renal insufficiency or associated comorbidities and inflammatory changes that develop during PD, results in a structural remodelling of the serosa. As a consequence, the filtering function of the serosa is lost and PD has to be replaced by another renal replacement therapy. Thorough knowledge of the morphology of peritoneal changes as well as of the risk factors is of paramount importance for therapeutic management and prognosis of PD patients. In order to take this into account, the German Registry In Peritoneal Dialysis (Deutsches Peritonealbiopsieregister, GRIP) was founded a few years ago, which now includes roughly 1700 biopsies, of which detailed clinical and histomorphological information was systematically acquired and collected.
CRIS-Team Scopus Importer:2020-09-18
Keywords: EPS; Fibrosis; Morphology; Peritoneal dialysis; Peritoneum